STUDI KEPADATAN TIKUS DAN EKTOPARASIT DI DESA JOMBLANG, KECAMATAN CANDISARI, KOTA SEMARANG TAHUN 2011 - Annashr, Nissa Noor; Santoso, Ludfi; Hestiningsih, Retno (Jurnal Ilmiah Ilmu Kesehatan: Wawasan Kesehatan, 2017)
Background: Rat is a rodent that can disrupt the lives and welfare of human beings. In the health sector, rats have an important role in the transmission of zoonotic diseases, because they contain ectoparasites. The purpose of this study was to determine the density of rats (trap success) and the types of ectoparasites in rats that were captured in the Jomblang Village, Candisari Subdistrict, Semarang.Method: This research was a descriptive study using survey method with cross sectional approach. Sample collection was done by placing single live trap in 50 houses, which every house got 2 single live traps.Results: The results showed that the number of rats that captured as 48 (trap success = 16 %), but only 43 has been successfully identified. Species of rat trapped consisted of Rattus tanezumi (48.84%), Rattus norvegicus (25.58%), Rattus norvegicus javanus (9.30%), Rattus exulans (2.33%), Bandicota indica (2.33%), Mus musculus (2.33%) and Suncus murinus (9.30%). Infested fleas were found on 30.23% rats, mostly on Rattus tanezumi (38.09%). All 16 fleas found in rats were Xenopsylla cheopis. The general flea index was < 2. Infested mites found on 44.19% rats, mostly on Rattus tanezumi (47.62%). From total 86 mites found in rats, there were two species of mites, Laelaps nutalli (83.72%) and Laelaps echidninus (16.28%).Conclusion: There were 7 species of rats, 1 species of mites and 2 species of fleas. Rattus tanezomi was the most infected rat species